A short guide to college writing - Barnet, Sylvan; Bellanca, Pat; Stubbs, Marcia (Penguin academics, 2013)
One of the high-quality, low-priced entries in Longman's Penguin Academics Series, "A Short Guide to College Writing" is a clear and authoritative brief rhetoric that emphasizes analysis, argument, and research in academic writing